O Desenho Cultural da Arquitetura Guarani - Carlos Zibel Costa (Pós: Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1993)
This work is about the guarani-mbya tribe dwelling, and its relation to their cultural characteristics, especially those found in the ritual and mythological traditions. The guarani-mbya way of life or tradition - teco - can just exist in their own place - tecoa - which means 'place where we live according to our own way of life' (Melia, 1988:104)